Selection in segregating populations of ornamental pepper plants (Capsicum annuum L.) using multidimensional scaling - Damasceno Costa, Maria do Perpetuo Socorro; Ramalho do Rêgo, Elizanilda; Alves Barroso, Priscila; da Silva, Anderson Rodrigo; Monteiro do Rêgo, Mailson (Revista Ceres, 2025)
Multidimensional scaling is a multivariate analysis technique that can be used to exploit genetic diversity, aiming at the selection of Capsicum genotypes with desirable characteristics for in-pot ornamental purposes. This work aimed to select genotypes with ornamental potential within F4 populations of ornamental pepper plants. Three F4 families were used (17.18, 30.16, and 56.8). The genotype distance matrixes between genotypes were estimated based on qualitative and quantitative descriptors, both separately, combining the standardized distances of Gower and Mahalanobis, respectively. The relation of the distance between genotypes was graphically studied through non-metric multidimensional scaling. Kruskal’ Stress was used as the measured misadjustment of the nMDS solution. There is genetic diversity within the analyzed families, allowing to practice selection. The selection in family 17.18 of genotypes 6 and 32 is recommended, as well as in family 30.16 of genotypes 22 and 4, and family 56.8 of genotypes 15 and 36, since they present important characteristics for ornamental purposes. The selection of genotypes is more efficient when using mixed data since it provides a more complete genetic diversity in an improvement program.